Analysis of Organizational Policy Changes In Subdistrict and Village Administration Within The Samarinda Ilir Subdistrict Government, Samarinda City - Asnar Asnar (Asian Journal of Social and Humanities, 2024)
This research was carried out in Samarinda Ilir District, Samarinda City with the aim of analyzing the policy of changing the organization of the sub-district and sub-district, as well as finding out the supporting and inhibiting factors in the policy of changing the organization of the sub-district and sub-district. This study uses quatitative approach, data collection was carried out by interview, observation and document analysis methods. The informants in this study were selected using  the purposive sampling method, namely the Head of the Organization Section of the Samarinda City Regional Secretariat, Samarinda Ilir Sub-district, Samarinda Ilir District Secretary, and the Head of Section in Samarinda Ilir District. The data analysis used is descriptive analytical analysis, where data is obtained through primary and secondary data sources and then analyzed gradually and continuously. The results of the study show that the policy of changing the organization of sub-districts and sub-districts in Samarinda Ilir District has been running effectively which is reviewed from the coordination of government administration and public services. However, this organizational change has not been effective in terms of community empowerment.